Efisiensi Lembaga Amil Zakat pada Masa Pandemi di Indonesia - Vina Septiana Permatasari; M Haris Hidayatulloh (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2021)
Amil Zakah Institution has been operating in Indonesia long before the covid-19 pandemic. This study aims to determine the efficiency of Amil Zakah Institutions which have been operating at the national level during the covid-19 pandemic. This study uses a non-parametrical quantitative approach. The data in this study are secondary data obtained from monthly reports which available in the magazines of the Amil Zakah Institutions. The analytical tools use in this research is data envelopment analysis (DEA). The use of DEA as an analytical tools in this study will be done toward two efficiency calculations which are partially and all of the zakah institution. The result found that amil zakah institutions operated efficiently during the covid-19 pandemic. It means the amil zakah institution has performed their function as a trustworthy and responsible collector and distributor of community social funds. The result of this study are expected to add references for the researchers, public, and the government about the efficiency of amil zakah institution which can help the government reduce the impact of covid-19 pandemic especially in the economic field.